PENGARUH KETERSEDIAAN FITUR DAN PERSEPSI RISIKO TERHADAP MINAT NASABAH MENGGUNAKAN MOBILE BANKING PADA BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU ULEE KARENG - Ulfanazirah; Ashal, Farid Fathony; Ridha, Ismail Rasyid (Journal of Sharia Economics, 2022)
The existence of Mobile Banking has a positive impact on the user because it drives transactions easier. This study aimed to specify the effect of feature availability and risk perception on customers' wishes to use Mobile Banking at BSI KCP Ulee Kareng. This study utilizes a quantitative research method with a purposive sampling technique in the form of distributing 65 questionnaires to the BSI KCP Ulee Kareng customers and utilizing multiple linear regression analysis techniques. The results show that the availability of features partially has an effect, while the other, risk perception, does not affect customers' wishes. However, the availability of features and risk perceptions simultaneously affect customers' wishes to use Mobile Banking. Keywords: Feature Availability, Risk Perception, and Customer Interest in Using Mobile Banking